Evaluation of the accuracy of two apex locators in endodontic treatment and retreatments: an ex vivo study - Yasser Samadi; Azadeh Harandi; Ali Soleymani; Saeid Tavanafar (Babol University of Medical Sciences, 2016)
Introduction: Working length determination is important in successful endodontic treatment and retreatment.This study evaluated the accuracy of two electronic apex locators Root ZX and Raypex®6 (EALs) in determining the electronic working length (EWL) of the root canals in endodontic treatment and retreatment. Materials and Methods: Access cavities were prepared on forty extracted, single-rooted human teeth and the actual working length (AWL) of the canals was determined. In the first phase of the study, primary EWL of un-instrumented teeth was measured and compared between two EALs. In phase II, all of the teeth were pre-flared and divided into the control(n=10) and the retreatment groups (n=30). Canals in the retreatment group were obturated by the lateral condensation technique using Gutta percha and sealer. After 15 days, gutta-percha was removed, and then the secondary EWL was recorded and compared between the two devices, in treatment and retreatment groups. Data were analysed by paired t-test and t-test. Results: Significant differences were found between both EALs in treatment and retreatment phases of the study (p<0.001).both EALs showed increased accuracy in retreatment group (p<0.001). However, no statistically significant differences were found between the control and retreatment groups in the second phase of the study for Root ZX (p = 0.929), and Raypex®6 (p=0.937). Conclusion: Accuracy of the two EALs was similar and acceptable. EWLs determined by Root ZX were closer to the AWL. The EWL determination after pre-flaring improved the accuracy of EALs and root canal obturation remnant materials did not have any clear effect on the accuracy of these EALs.